The Contingency Approach of Digitalization and Entrepreneurial Orientation on Smes Performance in Metal and Machinery Industry - Djou, LD Gadi; Udin, Udin; Lukiastuti, Fitri; Filatrovi, Eldes Willy (International Journal of Criminology and Sociology, 2022)
The ability to enter the global market has become a competitive necessity for many firms and one important for survival and growth in the era of globalization. At the same time, digitalization is transforming the locus of entrepreneurial opportunities and entrepreneurial practices, thus offering new perspectives on internationalization. When entering the global market, SMEs will require innovativeness capability, proactiveness, and risk-taking. However, there is a gap in the literature exploring the interplay of digitalization and entrepreneurial orientation in the internationalization process. The objective of the present study aims at developing insights that explain how SMEs in Slawi district in the metal and machinery industry can use the tactics and strategies associated with EO to achieve superior performance in the digitalization age. Results from a survey in 63 SMEs show that: 1) SMEs that display high levels of EO report a higher level of performance, 2) SMEs that display high levels of digitalization report a higher level of EO, 3) the relationship between EO and performance is moderated by digitalization and 4) the relationship between digitalization and performance is moderated by EO. These results indicate that for those firms, innovativeness capability, risk-taking, and proactiveness are crucial to their success in foreign markets. Instead, SMEs should develop a clear vision of digitalization that is characterized by innovation, being ahead of the competition, and a willingness to take risks.